INCREASING THE COMPETENCE OF TEACHERS OF SD KEPULAUAN SERIBU DKI JAKARTA PROVINCE THROUGH ASSISTANCE IN DEVELOPING PERFORMANCE ASSESSMENT INSTRUMENTS IN MATHEMATICS LEARNING - Sarifah, Iva (International Education Trend Issues, 2023)
This community service activity will be carried out in order to carry out one of the strategic plans of the State University of Jakarta and the Faculty of Education, namely Educational Technology. This community service activity will be carried out in the Thousand Islands Administrative District, DKI Jakarta Province. Problems related to teacher competency development faced by elementary schools in Kelapa Island, Seribu Islands Administrative District, DKI Jakarta Province in implementing the 2013 Curriculum, one of which is about assessment in learning. Teachers were still not optimal in measuring assessment instruments to measure attitudes, knowledge, and skills. In general, teachers rarely designed the instruments used in assessing skills, but instead used the instruments contained in the teacher's book. One of the efforts to help solved the problems faced by elementary school teachers in Kelapa Island, Seribu Islands Administrative District, DKI Jakarta Province is to provide assistance with performance development instruments in learning Mathematics. The object (target audience) of those community service activity are elementary school teachers in Kelapa Island, Seribu Islands Administrative District, DKI Jakarta Province. The partners involved were the Head of the Seribu Islands Administrative District Education Office, DKI Jakarta Province and the Head of SDN 01 Kelapa Island, Seribu Islands Administrative District, DKI Jakarta. The outputs of community service activities in the form of products/goods are: (a) performance assessment instruments in elementary mathematics learning; (b) publication of activity videos on Youtube; (c) partner's certificate regarding an increase in partner empowerment regarding teacher competence in developing performance assessment instruments in elementary mathematics learning; and (d) nameplate proof of the Assisted Village Cooperation. The service output is assistance in developing assessment instruments in elementary mathematics learning. Other outputs are articles in ISSN journals/ISSN national service seminars